Peran Pengendalian Mutu dalam Meningkatkan Inovasi dalam Pertumbuhan Bisnis Wirausaha pada Homelens Studio Sukabumi - Difa'a Kania R; Sopyan Saori; Adik Anov Permana; Khoirunnisa LMD (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the implementation of quality control in photography services at Homelens Studio in Sukabumi City to improve service quality and customer satisfaction. The research method used is descriptive qualitative with a flow chart approach to visualize the flow of the quality control process. The results of the study indicate that Homelens Studio has implemented five main stages in quality control, namely quality planning, quality control, monitoring, corrective action, and continuous improvement. The studio sets quality standards and operational procedures, conducts strict inspections of photo results, monitors the process periodically, and immediately follows up on deviations through root cause analysis and corrective actions. Continuous improvement is carried out through the PDCA cycle by relying on performance evaluation and customer feedback. In conclusion, Homelens Studio has succeeded in building an effective and adaptive quality control system to market needs, thereby increasing competitiveness through service innovations such as photobooth systems and photography service expansion.  Keywords: Photo Studio, Quality Control, PDCA, Photography Services, Homelens Studio